A Case of Prostatic Abscess with Malignant Lymphoma Involving the Prostate - Wataru Noguchi; Yoshihiro Inoue; Mana Fukushima (Case Reports in Urology)
Here, we report a case of prostatic abscess probably due to malignant lymphoma of the prostate. An 82-year-old man was referred to our hospital with chief complaints of urinary frequency and discomfort on urination. Antibiotics were prescribed, but the symptoms remained and intermittent fever appeared. The patient was diagnosed with prostatic abscess by computed tomography (CT). Digital rectal examination (DRE) revealed soft prostate, and thick pus was milked out from the extrameatus by prostatic massage. For drainage, we performed transurethral resection of the prostate (TURP). Drainage by TURP was successful as CT clearly showed reduction of prostatic abscess after the operation. Nevertheless, intermittent fever did not improve and the patient’s general condition deteriorated. The day before the patient died, histopathological analysis showed prostatic abscess probably due to malignant lymphoma of the prostate and incidental adenocarcinoma. This is the first report of prostatic abscess with malignant lymphoma involving the prostate.